2022
DOI: 10.3390/agriculture12020134
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Somatic Hybridization between Poncirus and Citrus Species Aiming to Create New Rootstocks

Abstract: Rootstocks are an important component for citrus adaptation to increasing biotic and abiotic stresses resulting from global climate change. There is a strong complementarity between Citrus species, which adapt to abiotic stresses, and Poncirus trifoliata and its intergeneric hybrids, which exhibit resistances or tolerances to major diseases and pests. Thus, symmetrical somatic hybridization between complementary diploid rootstocks of these two genera appears to be an efficient way to develop new tetraploid roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…Protoplast fusion is another technique used to create tetraploid somatic hybrids, theoretically adding dominant characters of both diploid parental genomes without sexual recombination (Grosser et al, 2000;Ollitrault et al, 2007;Dambier et al, 2011;Grosser and Gmitter, 2011). However, recent studies have revealed some chromosome instability and loss or duplication of substantial genomic regions (Ruiz et al, 2018;Dambier et al, 2022). These methods have been used for citrus rootstock breeding producing a wide range of tetraploid germplasm at intraspecific, interspecific, and even intergeneric levels.…”
Section: Implications For Triploid Scion and Tetraploid Rootstocks Br...mentioning
confidence: 99%
“…Protoplast fusion is another technique used to create tetraploid somatic hybrids, theoretically adding dominant characters of both diploid parental genomes without sexual recombination (Grosser et al, 2000;Ollitrault et al, 2007;Dambier et al, 2011;Grosser and Gmitter, 2011). However, recent studies have revealed some chromosome instability and loss or duplication of substantial genomic regions (Ruiz et al, 2018;Dambier et al, 2022). These methods have been used for citrus rootstock breeding producing a wide range of tetraploid germplasm at intraspecific, interspecific, and even intergeneric levels.…”
Section: Implications For Triploid Scion and Tetraploid Rootstocks Br...mentioning
confidence: 99%
“…Somatic hybridization has a significant advantage in citrus improvement because citrus plants could regenerate into whole plants [115]. Researchers were initially focused on produce male sterile and seedless citrus cybrids then tried more explorations of somatic hybridization covering improvement of techniques, citrus species, rootstocks resistance and so on [116][117][118][119]. Hybrid of somatic embryos between citrus and murraya puniculata were obtained by electrofusion, and further study revealed that percentage of multinucleated protoplast increasing linearly with increase the alternating voltage [117].…”
Section: Somatic Hybridization In Other Medicinal and Edible Plantsmentioning
confidence: 99%
“…Aiming to develop new tetraploid rootstocks harboring virtues of both parents, new intergeneric somatic hybrids were obtained by electrofusion between protoplasts of citrus, which adapt to abiotic stresses, and P. trifoliata hybrids, which exhibit resistances or tolerances to major diseases. Diploid cybrids and nuclear somatic hybrids were found, while symmetrical addition of the nuclear genomes of both parents was predominant at the whole genome level [118]. Asymmetrical somatic hybridization between two complementary diploid parents are thought be an efficient way to develop new tetraploid rootstocks for citrus stress adaptation [117][118][119].…”
Section: Somatic Hybridization In Other Medicinal and Edible Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several teams have widely used somatic hybridization to create tetraploid rootstocks combining characters of interest from different genetic resources. This method allows researchers to add genomes of two diploid genotypes without sexual recombination [42][43][44][45][46][47][48][49] and, therefore, to combine favorable dominant traits of the two parents. Recent genomic studies revealed chromosome instability in somatic hybrids, which can lead to substantial loss of genomic regions of parental lines [42].…”
Section: Introductionmentioning
confidence: 99%